Latest results from the UK trials evaluating prostate cancer screening and treatment: the CAP and ProtecT studies. - Lane, J; Hamdy, F; Martin, R; Turner, E; Neal, D; Donovan, J (2010)
The European Randomised Study of Screening for Prostate Cancer (ERSPC) demonstrated a significant reduction in prostate cancer-specific mortality. The ongoing Comparison Arm for ProtecT (CAP) cluster randomised controlled trial (RCT) evaluates prostate cancer screening effectiveness by comparing primary care centres allocated to a round of prostate specific antigen (PSA) testing (intervention) or standard clinical care. Over 550 centres (around 450,000 men) were randomised in eight United Kingdom areas (2002-2008). Intervention group participants were also eligible for the ProtecT (Prostate testing for cancer and Treatment) RCT evaluating active monitoring, radiotherapy and radical prostatectomy treatments for localised prostate cancer. In ProtecT, over 1500 of around 3000 men with prostate cancer were randomised from over 10,000 with an elevated PSA in around 111,000 attendees at clinics. Investigation of the psychological impact of screening in a sub-sample showed that 10% of men still experienced high distress up to 3 months following prostate biopsies (22/227), although most were relatively unaffected. The risk of prostate cancer with a raised PSA was lower if urinary symptoms were present (frequent nocturia odds ratio (OR) 0.44, 95% confidence interval (CI) 0.22-0.83) or if a repeat PSA decreased by > or = 20% prior to biopsy (OR 0.43, 95% CI 0.35-0.52). Men aged 45-49 years attended PSA clinics less frequently (442/1299, 34%) in a nested cohort with a cancer detection rate of 2.3% (10/442). The CAP and ProtecT trials (ISRCTN92187251 and ISRCTN20141217) will help resolve the prostate cancer screening debate, define the optimum treatment for localised disease and generate evidence to improve men's health.